Rental Transaction by Conduct (without Using Words) from The Perspective of Iranian Jurisprudence and Law - Saeed Kheradmandi (آموزه‌‌های فقه مدني, 2020)
The rental contract in jurisprudence and legal regulations is an ownership (proprietary) nature, so in rental transaction by conduct (without using words), the conduction of such a nature is discussed with external acts. Most jurists do not consider a transaction by conduct (without using words) to have an ownership (proprietary) effect, and as a result, they do not consider the sale and rental transaction by Conduct (without using words) which cause the transfer of benefits and the object of sale. In the lease of objects, according to Article 468 of the Islamic Penal Code, it seems difficult to accept the rental transaction by conduct (without using words), and it can be said, according to Article 494 of the Islamic Penal Code that rental transaction by conduct (without using words) has not been accepted. In the Law on Landlord-Tenant (tenant and the landlord act) Relations of 1997 (1376 in the Solar Hijri calendar), the method of writing legal articles is such that it should be ruled that the rental transaction by conduct (without using words) not valid. Although, in other cases, the rental transaction by conduct (without using words) has not been explicitly accepted, based on the absoluteness of indications, and according to the various theories that have been proposed and raised regarding the absoluteness of the contract form, it is possible to rule on the validity of the rental transaction by conduct (without using words) in doubtful cases.